FROM TOUR TO PROBLEM SOLVING: EVOLUTION OF LIBRARY INSTRUCTION PROGRAMMES IN TUN SERI LANANG LIBRARY UNIVERSITI KEBANGSAAN MALAYSIA - Salim, Juhana; Salim, Juhana (Malaysian Journal of Library and Information Science, 2017)
Academic librarians play an important role in meeting the complex challenges of contemporary education by concerning themselves not only with supplying information sources but also in designing and managing proper library instruction programmes. This article gives an account of the library instruction programmes managed at the Tun Seri Lanang Library (TSLL), Universiti Kebangsaan Malaysia (UKM). To impart library skills, the library developed six basic instruction programmes. These include the Tanggaton Tun Seri Lanang, Information search process through problem solving and the Tun Seri Lanang Clinic. The six basic instruction programmes were constantly evaluated and changes made to the modules after considering feedback from participants.